Acerca del plan Colombia - Deas, Malcom (Sociedad y Economía, 2001)
The essay presents the case in defense of a concept that has little support in Colombia: namely the continuing military support to this country within the framework of Plan Colombia. The analysis begins with a look at the basic elements of the armed conflict and presents a critique of the traditional arguments usually given in relation to the genesis and continuing developments in the conflict. The essay proposes a different interpretation with respect to the motives of the guerrilla movement and of their right wing opponents in the paramilitary groups. The idea that the military assistance provides an ‘opportunity for warfare’ is considered a very cynical way to look at the present situation. Rather the military assistance is seen within the framework of an alternative approach. The success (or failure) of the military assistance will determine in large degree the outcome of the present peace negotiations.